Continuous assessment in post-secondary teacher training in Ghana: a case study evaluation - Akyeampong, Albert Kwame (1997)
The importance of and preference for assessing learning outcomes using a variety of assessment techniques and containing data from many sources, rather than the sole dependence on the one-shot examination, has long been recognised worldwide. This has led to major assessment policy changes in both developed and developing countries. In Ghana, this change has led to the introduction of continuous assessment at all levels of secondary schooling and post-secondary teacher training, to operate in parallel with external examinations. Although in Ghana evaluation studies of continuous assessment have been conducted for the secondary school level, none has so far been done for the post-secondary teacher training level. The purpose of this research was therefore, to examine the nature and scope of activities and problems that have to do with the practice of continuous assessment at the postsecondary teacher training level in Ghana. The research also examined the training and guidance provided for those undertaking continuous assessment, and the impact of the new assessments upon teaching and learning. A qualitative case study was conducted in three selected training colleges from the months, February to March of 1996 and January of 1997. The selected colleges were considered to be a fair representation of the teacher training college system in Ghana. The field research also included interviews with key officials associated with the postsecondary teacher training system. Findings from the multi-site case study evidence were presented and analysed for their significance. The findings of the research suggest that, many problems continue to threaten the benefits derivable from using continuous assessment in assessing students in the training colleges. The key findings that emerged as significant includes: operational and structural conditions in the colleges, professional support systems for tutors to carry out continuous assessment, tutor competency in assessment and considerations rooted in the values and beliefs of tutors about assessment which define their assessment culture and agenda. Evidence from those findings was then used as a basis for conclusions about improving continuous assessment in post-secondary teacher training, in Ghana. Recommendations for policy implementation and potential areas for further research were also made.